Analysis of the Educational Administration of the Public Educational Centers of Andalusia (Spain): The Role of the Manager in the Face of New Social Challenges - Maximiliano Ritacco-Real; Daniel Garrote-Rojas; Francisco Javier Jiménez-Ríos; Francisco Miguel Rodríguez-Martínez (MDPI AG, 2022)
The advance and influence of neoliberalisation processes has changed the way of understanding and managing the educational system under a New Public Management (NPM) of education that integrates the values of the free market, competitiveness, accountability, external evaluation, etc. The objective of this work is to analyse Andalusian headteachers' perceptions of their professional practices from within the context of neoliberal and neo-conservative processes. The methodology used is based on a qualitative research approach, where we analyse the implications of neoliberal processes and NPM in the school principalship in Andalusia (Spain). The sample of participants was consolidated into 15 principals belonging to public high schools. For data collection, in-depth interview was used. Information analysis applies content analysis and its assembly with the grounded theory. The results are expressed in four categories that refer to the implications of neoliberal processes and NGP in the school principalship. There is a tendency to redefine the role of the headteacher as a manager. The discussion and conclusions point out how the neoliberal processes and the NPM are reconfiguring the school principalship towards a "manager-administrator" profile, a management instrument with administrative functions and an agent for assessment in the school. In this context, there are also processes of confrontation and discomfort with these transformations in the principal's role.